STRATEGI HUMAS, PROTOKOL DAN PUBLIKASI DPRD KABUPATEN BADUNG DALAM MEWUJUDKAN GOOD GOVERNANCE DI KABUPATEN BADUNG - Erviantono, Tedi; Maharani, Pande Putu Regina; Pramana, Gede Indra (Jurnal Nawala Politika, 2023)
The purpose of this study was to determine the role of Public Relations and Protocol of the Badung Regency DPRD in maintaining the performance and image of the Badung Regency DPRD. Badung DPRD Public Relations plays a fairly important role in the correlation of internal and external relations. The activities of the leaders and members of the board are always publicized and will certainly cause stigma from the community. To suppress bad things, Badung Regency DPRD Public Relations needs to have a strategy in carrying out its duties and functions. This research was made to find out the strategy used by the Public Relations and Protocol Coordinator of the Badung Regency DPRD and the researchers participating as participant observers, so that the research could be more focused. This research is a descriptive qualitative with data collection techniques in the form of participant observation, interviews and supported document data which will be processed later. The results of this study indicate that the Public Relations, Protocol and Publication of the Badung Regency DPRD carry out their role very well, namely building functional relationships with the public, both institutionally by establishing partnerships with the media such as mass media, print and online in order to publish news on DPRD activities. Keywords: Strategy, Public Relations, Activities of DPRD Badung Regency, Local Government.